Inferior Hip Dislocation in a 60-Year-Old Man; a Case Report - Yeganeh, Ali; Tavakoli, Nader; Soleimani, Mohammad; Taheri, Seyed Nima; Cheraghiloohesara, Sahand (Archives of Academic Emergency Medicine, 2022)
Inferior hip dislocation or luxatio erecta femoris is among the rarest hip dislocations, which has been described in limited studies. The patients usually present with their hip in flexion, abduction, and external rotation. Hip dislocation is an orthopedic emergency, and a reduction needs to be performed promptly to avoid devastating complications such as avascular necrosis. Here, we present a rare case of inferior hip dislocation in a 60-year-old man following a car-motorcycle collision. The patient presented to the emergency department with left hip flexion, abduction, external rotation, and inability to move his leg due to pain. Closed reduction under procedural sedation was attempted in the emergency department once, which was unsuccessful. The patient was then taken to the operating room for another attempt of closed reduction under general anesthesia. The patient was discharged after two days with pin traction and double crutches. After two weeks, the pin was removed, and full weight-bearing was permitted. After 12 weeks, the patient had mild pain with unusual activity and slight limping; however, imaging revealed no signs of any complications.